About a free school: Summerhill - Fortunato, Ivan (Revista Hipótese, 2017)
I have always hated schooling, so I cannot explain why I went to the university to become a school teacher. I ran into “Summerhill” by accident when I was passing by a bookstore of old/used/rare books and it cost me only pocket change. Unfortunately, I had never even heard about the possibility of a free school during the years I have spent at the University. [...]